A Novel Liquid-Liquid Extraction for the Determination of Sertraline in Tap Water and Waste Water at Trace Levels by GC-MS - Kocoglu, Elif Seda; Bakirdere, Sezgin; Keyf, Seyfullah (SPRINGER, 2017)
A simple, green and fast analytical method was developed for the determination of sertraline in tap and waste water samples at trace levels by using supportive liquid-liquid extraction with gas chromatography-mass spectrometry. Different parameters affecting extraction efficiency such as types and volumes of extraction and supporter solvents, extraction period, salt type and amount were optimized to get lower detection limits. Ethyl acetate was selected as optimum extraction solvent. In order to improve the precision, anthracene-D10 was used as an internal standard. The calibration plot of sertraline was linear from 1.0 to 1000 ng/mL with a correlation coefficient of 0.999. The limit of detection value under the optimum conditions was found to be 0.43 ng/mL. In real sample measurements, spiking experiments were performed to check the reliability of the method for these matrices. The spiking experiments yielded satisfactory recoveries of 91.19 +/- 2.48%, 90.48 +/- 5.19% and 95.46 +/- 6.56% for 100, 250 and 500 ng/mL sertraline for tap water, and 85.80 +/- 2.15% and 92.43 +/- 4.02% for 250 and 500 ng/mL sertraline for waste water.
Keywords: Sertraline; Supportive liquid-liquid extraction; GC-MS; Internal standard; SOLID-PHASE EXTRACTION; CHROMATOGRAPHY-MASS SPECTROMETRY; SEROTONIN REUPTAKE INHIBITORS; PERSONAL CARE PRODUCTS; ACTIVE METABOLITES; SENSITIVE DETERMINATION; HUMAN SERUM; PHARMACEUTICALS; ANTIDEPRESSANTS; MICROEXTRACTION; Environmental Sciences & Ecology; Toxicology